(untitled) (Journal of actual problems of jurisprudence, 2026)
In the framework of this article, a scientific study of copyright infringement has been conducted: plagiarism and coercion to co-authorship. Despite the frequent situations with accusations of plagiarism, however, attention should be paid to the lack of a legislative definition of the terms "plagiarism", "originality", "citation". The article also analyzes cases of coercion of reviewers to co-author articles that are sent for review within the framework of editorial policy of scientific journals. The author raises the question whether these actions of the reviewer are considered copyright infringement in accordance with Article 198 of the Criminal Code of the Republic of Kazakhstan. The author of the article raises questions about conducting forensic linguistic (philological) and scientific examinations in order to protect their rights and legitimate interests of the authors. Analyzing these issues, the author comes to the conclusion that the answer to these challenges should be formulated not only by the doctrine of civil law, but also by judicial expertise and criminal law. In this regard, according to the author, a clear understanding of plagiarism and coercion to co-authorship should be developed in the criminal law doctrine, and it should also be understood that as a result of plagiarism and coercion to co-authorship, the personal non-property rights of authors are violated. The author concludes that two court cases may arise regarding the protection of the right of authorship as a personal non-property right.: 1) civil, that is, filing a claim to challenge authorship, and 2) criminal, that is, attribution of authorship or coercion to co-authorship. The author of this article proposed to introduce administrative liability for plagiarism and coercion to co-authorship and, accordingly, editorial articles in the Code of Administrative Offenses of the Republic of Kazakhstan. In this regard, it is proposed to delete paragraph 1 of Article 198 of the Criminal Code of the Republic of Kazakhstan, which provides for the formal composition of a criminal offense. Keywords: plagiarism, originality, borrowing, coercion, co-authorship, academic fraud, scientific research, reviewer.